Methyl Jasmonate Applications From Flowering to Ripe Fruit Stages of Strawberry (Fragaria × ananassa ‘Camarosa’) Reinforce the Fruit Antioxidant Response at Post-harvest - Zuñiga, Paz E.; Castañeda, Yasna; Arrey-Salas, Oscar; Fuentes, Lida; Aburto, Felipe; Figueroa, Carlos R. (Frontiers in Plant Science, 2020)
Preharvest applications of methyl jasmonate (MeJA) have been shown to improve post-harvest fruit quality in strawberry fruit. However, the effectiveness of consecutive field applications at different phenological stages on the reinforcement of the antioxidant capacity remains to be analyzed. To determine the best antioxidant response of strawberry (Fragaria × ananassa ‘Camarosa’) fruit to different numbers and timing of MeJA applications, we performed three differential preharvest treatments (M1, M2, and M3) consisted of successive field applications of 250 μmol L–1 MeJA at flowering (M3), large green (M2 and M3), and ripe fruit stages (M1, M2, and M3). Then, we analyzed their effects on fruit quality parameters [firmness, skin color, soluble solids content/titratable acidity (SSC/TA) ratio, fruit weight at harvest, and weight loss] along with anthocyanin and proanthocyanidin (PA) accumulation; the antioxidant-related enzymatic activity of catalase (CAT), guaiacol peroxidase (POX), and ascorbate peroxidase (APX); the total flavonoid and phenolic contents, antioxidant capacity, and ascorbic acid content (AAC) during post-harvest storage (0, 24, 48, and 72 h). We also evaluated the effect on lignin, total carbon and nitrogen (%C and N), lipid peroxidation, and C and N isotopes signatures on fruits. Remarkably, the results indicated that MeJA treatment increases anthocyanin and PA contents as well as CAT activity in post-harvest storage, depending on the number of preharvest MeJA applications. Also, M3 fruit showed a higher AAC compared to control at 48 and 72 h. Noticeably, the anthocyanin content and CAT activity were more elevated in M3 treatment comparing with control at all post-harvest times. In turn, APX activity was found higher on all MeJA-treated fruit independent of the number of applications. Unlike, MeJA applications did not generate variations on fruit firmness and weight, lignin contents,% C and N, and in lipid peroxidation and water/nitrogen use efficiency according to C and N isotope discrimination. Finally, we concluded that an increasing number of MeJA applications (M3 treatment) improve anthocyanin, PA, AAC, and CAT activity that could play an essential role against reactive oxygen species, which cause stress that affects fruits during post-harvest storage.